Preimplantation Genetic Testing for Polygenetic Conditions: A Legal, Ethical, and Scientific Challenge - Ginod, Perrine; Dahan, Michael H. (Seminars in Reproductive Medicine, 2024)
The recent commercialization of the Embryo Health Score (EHS), determined through preimplantation genetic testing for polygenic conditions, offers the potential to select embryos with lower disease risk, thus potentially enhancing offspring longevity and health. Lately, Orchid Health company increased testing from less than 20 diseases to more than 900+ conditions for birth defects. However, the “geneticization” of phenotype estimates to a health state erases the environmental part, including the in vitro fertilization potential risks, questioning its scientific usefulness. EHS is utilized in countries with minimal regulatory oversight and will likely expand, while it remains illegal in other countries due to ethical and legal dilemmas it raises about reproductive autonomy, discrimination, impacts on family dynamics, and genetic diversity. The shift toward commercialized polygenic embryo screening (PES) redefines healthcare relationships, turning prospective parents into consumers and altering the physician's role. Moreover, PES could increase social inequalities, stigmatize those not born following PES, and encourage “desirable” phenotypic or behavioral traits selection, leading to ethical drift. Addressing these issues is essential before further implementation and requires a collaborative approach involving political, governmental, and public health, alongside geneticists, ethicists, and fertility specialists, focusing on the societal implications and acceptability of testing for polygenic traits for embryo selection.
Keywords: polygenic risk score; Embryo Health Score; embryo selection; ethics; legislation